Use of intravascular ultrasound for optimal vessel sizing in chronic total occlusion percutaneous coronary intervention - Blessing, Recha; Buono, Andrea; Ahoopai, Majid; Geyer, Martin; Knorr, Maike; Brandt, Moritz; Steven, Sebastian; Drosos, Ioannis; Muenzel, Thomas; Wenzel, Philip; Gori, Tommaso; Dimitriadis, Zisis (Frontiers in Cardiovascular Medicine, 2022)
Aim: The aim of this study is to provide evidence how a standardized intravascular ultrasound (IVUS) use impacts stent size choice in the setting of chronic total occlusion (CTO) percutaneous coronary intervention (PCI) compared to visual estimation. Methods and results: Data of 82 consecutive patients who had successfully undergone IVUS-guided revascularization of a CTO at the University Medical Center Mainz were analyzed. Angiography-based stent size prediction for the proximal and distal vessel were compared to the implanted stent diameter after IVUS assessment. Angiography-based stent size prediction for the proximal vessel was 3.09±0.41whereas IVUS use demonstrated larger vessel diameter, resulting in a larger implanted stent diameter (3.24± 0.45, p < 0.001). Proximal vessel stent size prediction was underestimated in the majority of patients by angiographic estimation. Angiography-based stent size prediction for the distal vessel was 2.79±0.38 whereas IVUS use demonstrated larger vessel diameter, resulting in a larger implanted stent diameter (2.92±0.39 p < 0.001). Conclusions: Pre-Stent IVUS assessment in CTO PCI provides important information of vessel morphology and size. Angiography-based stent size prediction for the proximal and the distal vessel was frequently underestimated, IVUS use demonstrated larger vessel diameter, resulting in significant larger implanted stent diameters.